Effects of dietary supplements on adaptions to endurance training - Rothschild, J. A.; Bishop, D. J. (Sports Medicine, 2019)
Endurance training leads to a variety of adaptations at the cellular and systemic levels that serve to minimise disruptions in whole-body homeostasis caused by exercise. These adaptations are differentially affected by training volume, training intensity, and training status, as well as by nutritional choices that can enhance or impair the response to training. A variety of supplements have been studied in the context of acute performance enhancement, but the effects of continued supplementation concurrent to endurance training programs are less well characterised. For example, supplements such as sodium bicarbonate and beta-alanine can improve endurance performance and possibly training adaptations during endurance training by affecting buffering capacity and/or allowing an increased training intensity, while antioxidants such as vitamin C and vitamin E may impair training adaptations by blunting cellular signalling but appear to have little effect on performance outcomes. Additionally, limited data suggest the potential for dietary nitrate (in the form of beetroot juice), creatine, and possibly caffeine, to further enhance endurance training adaptation. Therefore, the objective of this review is to examine the impact of dietary supplements on metabolic and physiological adaptations to endurance training.